Snus users: intraoral lesions, biofilm properties, communication and treatment strategies - Miluna, Sintija; Kroica, Juta; Pilmane, Mara; Skadins, Ingus; Koka, Rudite; Rostoka, Dagnija (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Objective: The link between snus, periodontal diseases and oral malignancy is still in question in different literature. This study aims to explore the impact of snus on mucosal lesions and oral malignancy along with evaluation of strategies for snus cessation and approaches to communication with patients. Methods: A questionnaire about tobacco consumption habits was made. A heavy snus group, a light snus group and a control group were made. Oral biopsy samples were tested for protein gene product 9.5, tissue inhibitor of matrix metalloproteinase 2, chromogranin A and B, matrix metalloproteinase 2, interleukin-1, interleukin-10 using immunohistochemical techniques. Periodontal pocket biofilms were tested with combined polymerase chain reaction and were subsequently analyzed in order to determine the presence of pathogenic periodontal bacteria, such as Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola and Prevotella intermedia. Results: Biopsy results showed cellular disorganization, apoptosis, hyperkeratosis and prevalence of keratotic seborrhea in the area of snus sachets. Microbiological examination revealed the presence of periodontal pathogens in the snus users group. High concentration of pathogenic periodontal bacteria Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis and Prevotella intermedia was found in groups of both heavy and light snus users, yet they were absent in the samples of the control group. High concentration of Tannerella forsythia and Treponema denticola was also found in the groups of heavy and light snus users, whereas they were present in samples of only two patients of the control group. Conclusions: Snus changes cell function, it can lead to oral malignancy and promote periodontal disease regardless of the frequency and amount of snus used.